Predictors for Prolonged Intensive Care Unit Stay After Adult Orthotopic Liver Transplantation - Aycan Kundakcı; Arash Pirat; Özgür Kömürcü; Adnan Torgay; Hamdi Karakayalı; Gülnaz Arslan; Mehmet Haberal (Galenos Yayinevi, 2011)
Objective: Intensive care unit (ICU) stay consumes physical and financial resources and may increase the risk of complications and possibly mortality. The purpose of this study was to evaluate the factors predicting prolonged ICU length of stay (LOS) after orthotopic liver transplantation (OLT). Materials and Methods: We reviewed the data of 112 adult patients who underwent OLT between January 2000 and February 2009. The data included the demographic and clinical features, preoperative laboratory values, intraoperative hemodynamic parameters and transfusions, and mortalities. Prolonged ICU LOS was defined as more than 3 days stay in the ICU after OLT. Results: Out of 112 patients 59 (53%) of them required prolonged ICU LOS. Patients who required prolonged ICU LOS compared to those who did not had higher model for end stage liver disease (MELD) and Child-Pugh scores (p<0.001), had a lower mean preoperative hemoglobin level (p=0.04), had a higher mean preoperative blood urea nitrogen level (p=0.013), less frequently had coronary artery disease (p=0.046), required higher amounts of blood products transfusions intraoperatively (p=0.004), and had a longer duration of anesthesia (p=0.010). Multivariate logistic regression revealed that only higher MELD scores (odds ratio: 1.4, CI%95:1.2-1.7, p=0.010) was an independent risk factor for prolonged ICU stay after liver transplantation Patients who had developed renal failure in the early postoperative period according to the RIFLE criteria had stayed in the ICU longer [74% (23) vs 44%(36), p=0.006]. Patients who had stayed in the ICU for more than 3 days had higher rates of mortalities [41% (24) vs 9% (5), p<0.001]. Conclusion: In conclusion, 53% of our liver transplant recipients required prolonged ICU stay postoperatively and a higher MELD score was an independent risk factor for prolonged ICU requirement. (Journal of the Turkish Society of Intensive Care 2011; 9: 14-8)